2016
DOI: 10.15587/2312-8372.2016.86137
|View full text |Cite
|
Sign up to set email alerts
|

Surge arrester modeling using Micro-Cap

Abstract: в умовах польоту і керувати роботою БПС відповідно до виявлених показників. література 1. Дрон-почтальон Drone.UA и Новая Почта в галлерее инноваций HUB 4.0 [Электронный ресурс] // Drone.UA.-15.05.2016.-Режим доступа: \www/URL: http://drone.ua/ delivery-drone/ 2. Красномовец, П. «Укрпочта» провела тестовую доставку посылки с помощью израильского дрона [Электронный ресурс] / П.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This study is a continuation of the authors' work [3] on the simulation of the surge arrester using the Micro-Cap circuit simulator. The main research circuits are shown on Fig.…”
Section: Research Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…This study is a continuation of the authors' work [3] on the simulation of the surge arrester using the Micro-Cap circuit simulator. The main research circuits are shown on Fig.…”
Section: Research Resultsmentioning
confidence: 95%
“…The main research circuits are shown on Fig. 1 and represent two equivalent ways of surge arrester simulation using the evaluation version of the Micro-Cap circuit simulator [3]. …”
Section: Research Resultsmentioning
confidence: 99%
See 3 more Smart Citations